Binding of lambda carrageenan to bovine serum albumin and non-equilibrium effects of complexation. (May 2022) - Antonov, Yurij A.; Moldenaers, Paula; Cardinaels, Ruth
Abstract: Binding of lambda carrageenan (lCG) to bovine serum albumin (BSA) and the effect of the formation path, namely mixing (M) at specific pH versus titration (T) from a neutral mixture, on complexation have been studied using turbidimetry, phase analysis, dynamic light scattering, confocal laser scanning and bright-field optical microscopy, circular dichroism and fluorescence measurements. The sizes and shape of the complex particles formed under T-conditions differ significantly from those obtained under M-conditions, and at maximal complexation T-complexes contain significantly less lCG as compared to M-complexes. At a pH below pIBSA phase analysis reveals two domains of q corresponding to an approximately constant lCG/BSA weight ratio in the complex phase q* (domain I), and a decreasing q* (domain II). Binding stoichiometries at pH 4.2 and 4.7 are 1:77 and 1:119 mole lCG/mole BSA. The yield of BSA in the complex phase is higher than 98% at pH 4.2 and 4.7, and the complexes form and are stable in the presence of 1.0M–1.5M NaCl. The interaction did not lead to protein denaturation or significant changes in the tertiary and secondary structure and illustrates an enhancement of the hydrophobicity of the protein within the complex particles. At pH 5.2 (pH on the wrong side of PIBSA ) up to 37.6% BSA was bound to lCG, and the weight ratio of lCG/BSA in the complex particles (q*) was weakly dependent on q in the complete q range studied. The molecular origin of the unusually strong interaction between lCG and BSA is discussed. Graphical abstract: Image 1 Hightlights: T- and M-complexes of BSA with lCG differ significantly in their average size and shape. The compositions of the T- and M-complexes differ at the same q and pH of the mixture. At pH < pI, complexes are formed and stable even at ionic strength ≥1.5. At pH qMax, the q * values in the complex particles decrease with increasing q. At pH 5.2, insoluble complexes are formed and stable at ionic strength up to 0.3.